Statically Stable Walking Gait Planning of a Kind of Exoskeleton Walking Aid Robot - Yi Zikai; Li Juan; Li Weida; Hu Haiyan; Li Chunguang (Jixie chuandong)
A 8-DOF exoskeleton walking aid robot is designed,which can complete the walking motion in the sagittal plane. And the center of gravity can transfer in the frontal plane during walking through the transfer module of the foot center of gravity. The analysis of kinematics modeling is carried on to solve the relationship between the joint angle and the center of gravity of trajectory. Based on the theory of focus projection method,a gait planning method is proposed for the statically stable walking of the robot based on the gravity center track. The joint trajectory is solved and stability margin is verified through MATLAB simulation. The simulation results show the exoskeleton robot can walk with static stability.